A SYSTEMATIC REVIEW OF INDONESIAN HIGHER EDUCATION STUDENTS’ AND GRADUATES’ WORK READINESS - Nugroho, Novianto Eko; Irianto, Jusuf; Suryanto, Suryanto (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2024)
This literature review aims to determine the work readiness of undergraduate graduates to meet the qualifications required by employers in the world of work. The method used in this paper involved searching for all studies that examined work readiness and were published from 2019 to 2023. 5 out of 200 studies found on Google Scholar and Scopus were included in this review. Research findings show that programs in higher education, including internships and soft skills training, play an important role in increasing graduates’ work readiness, demonstrating that the MBKM Program has effectively developed the skills and competencies required by the world of work. Research discussions highlight that these programs, including internships and soft skills training within the MBKM Program, are crucial for ensuring the relevance of education to job market needs. This research presents novelty by exploring and identifying the factors that influence the job readiness of prospective undergraduate graduates after participating in the Independent Campus Learning Program (MBKM), thus offering a new perspective in the context of higher education in Indonesia. The implications of this research are significant for curriculum development and learning programs in universities, which must continue to develop programs that support the development of soft skills and hard skills to increase graduates’ work readiness.